A Body‐Temperature‐Triggered In Situ Softening Peripheral Nerve Electrode for Chronic Robust Neuromodulation - Xueyang Ren; Wenjie Tang; Yuehui Yuan; Shisheng Chen; Fangzhou Lu; Jinyang Mao; Jidan Fan; Xufeng Wei; Ming Chu; Benhui Hu (Advanced Science)
Abstract Implantable peripheral nerve electrodes are crucial for monitoring health and alleviating symptoms of chronic diseases. Advanced compliant electrodes have been developed because of their biomechanical compatibility. However, these mechanically tissue‐like electrodes suffer from unmanageable operating forces, leading to high risks of nerve injury and fragile electrode‐tissue interfaces. Here, a peripheral nerve electrode is developed that simultaneously fulfills the criteria of body temperature softening and tissue‐like modulus (less than 0.8 MPa at 37 °C) after implantation. The central core is altered from the tri‐arm crosslinker to the star‐branched monomer to kill two birds (close the translation temperature to 37 °C and decrease the modulus after implantation) with one stone. Furthermore, the decreased interfacial impedance (325.1 ± 46.9 Ω at 1 kHz) and increased charge storage capacity (111.2 ± 5.8 mC cm−2) are achieved by an in situ electrografted conductive polymer on the strain‐insensitive conductive network of Au nanotubes. The electrodes are readily wrapped around nerves and applied for long‐term stimulation in vivo with minimal inflammation. Neuromodulation experiments demonstrate their potential clinical utility, including vagus nerve stimulation in rats to suppress seizures and alleviation of cardiac remodeling in a canine model of myocardial infarction.